Pitfalls of X‐chromosome inactivation testing in females with Fabry disease. Issue 7 (26th March 2022) - Řeboun, Martin; Sikora, Jakub; Magner, Martin; Wiederlechnerová, Helena; Černá, Alena; Poupětová, Helena; Štorkánova, Gabriela; Mušálková, Dita; Dostálová, Gabriela; Goláň, Lubor; Linhart, Aleš; Dvořáková, Lenka
Abstract: Fabry disease (FD) is an X‐linked lysosomal storage disorder caused by mutations in the GLA gene encoding alpha‐galactosidase A (AGAL). The impact of X‐chromosome inactivation (XCI) on the phenotype of female FD patients remains unclear. In this study we aimed to determine pitfalls of XCI testing in a cohort of 35 female FD patients. XCI was assessed by two methylation‐based and two allele‐specific expression assays. The results correlated, although some variance among the four assays was observed. GLA transcript analyses identified crossing‐over in three patients and detected mRNA instability in three out of four analyzed null alleles. AGAL activity correlated with XCI pattern and was not influenced by the mutation type or by reduced mRNA stability. Therefore, AGAL activity may help to detect crossing‐over in patients with unstable GLA alleles. Tissue‐specific XCI patterns in six patients, and age‐related changes in two patients were observed. To avoid misinterpretation of XCI results in female FD patients we show that (i) a combination of several XCI assays generates more reliable results and minimizes possible biases; (ii) correlating XCI to GLA expression and AGAL activity facilitates identification of cross‐over events; (iii) age‐ and tissue‐related XCI specificities of XCI patterning should be considered.